Metafísica de la persona y del diálogo : Hegel, Habermas y Santo Tomás - Sambataro, Patricia N. (Sapientia, 2016)
The present work has as purpose to manifest in the first place the theme of the person in the Hegel’s Science of Logic, secondly to show the topics of the dialogue and communication in an author of idealistic roots as is Habermas and, by last, to present the subjects of person and dialogue in St. Thomas Aquinas’ metaphysics. It is of standing out that any philosophical theme that Aquinas analyze is invariably inserted into a metaphysical and theological appreciation, because in this consists the very identity of the Thomasian thought. It is then only in fidelity to it that the teaching of St. Thomas can provide today a valuable contribution to important issues such as the person and the dialogue, and also enlighten and serve of discernment regarding the proposals of modern and contemporary authors such as Hegel and Habermas.